Evaluation of intraocular pressure changes in wind instrument musicians in the State of Sergipe, Brazil (Research, Society and Development, 2022)
Introduction: The act of playing a wind instrument involves performing a mechanism similar to the Valsalva maneuver (MV). This maneuver generates organic responses that influence the fluctuation of intraocular pressure (IOP). The increase in IOP is the main risk factor for the development of Glaucoma, the first cause of irreversible blindness in the world. This study aims to observe changes in IOP in musicians playing wind instruments, of high and low resistance, in the different phases of musical performance. The group involved in the study consisted of professional musicians from the state of Sergipe, Brazil, who play wind instruments from high to low resistance. Methods: The IOP measurement procedure was performed using the applanation tonometry technique. Results: 84 male and female participants were included, with a mean age of 37.3 years - standard deviation (SD= 9.2), five had a previous personal history of glaucoma diagnosis, 3 had diabetes mellitus and nine had arterial hypertension. Twenty-eight of them had a previous family history of glaucoma. The mean IOP, in right eyes, of the measurements taken before the musical performances, was 13.1 mmHg (SD= 2.3) and after, 14.5 mmHg (SD= 2.6), noting relevant increase, with p-value < 0.001 and R -0.690. In left eye measurements, the mean IOP, before playing, showed 13.3 mmhg (SD= 2.1), after, 14.5 mmHg (SD= 2.3). Conclusion: Statistically, there were no huge variations in IOP, although there are isolated increases in certain patients, which in the long term constitutes a risk factor for the development of glaucoma.